Revealing the Association of Pharmacist’s Job Satisfaction and Organizational Behavior Citizenship in Taiwan - Chen, Ying-hsuan; Wang, Tai-Chi; Pan, Frank F. C (Journal of Asian Business Strategy, 2018)
Organizational citizenship behavior (OCB) was critical to the organization’s operation effectiveness and success. Literature had proved that job satisfaction is one of the major contributors to OCB. We examined this relationship with 105 pharmacists who attended in an annual meeting. Test results indicated that job satisfaction affected mostly on the conscientiousness and altruism. Jos satisfaction explained 43.7% of the OCB variance. This study confirmed the linkage between job satisfaction and OCBs. We suggested providing special incentive program to incumbent pharmacist’s job satisfaction, and then to foster the pharmacist’ OCB.